Revolusi Islam Iran - Amin, Ismail (Indonesia Center for Middle East Studies, 2025)
The 1979 Islamic Revolution in Iran stands as one of the most complex and challenging revolutions in modern history, as it not only overthrew the Pahlavi monarchy but also established an Islamic republic that integrates religious and political values. This article departs from the question: to what extent can the Iranian Islamic Revolution be explained through theories of social revolution and/or religious revolution? To address this, the study compares two theoretical perspectives: Theda Skocpol’s theory of social revolution, which emphasizes structural and institutional factors, and Imam Ali Khamenei’s concept of religious revolution rooted in Qur’anic values and spirituality. Using a qualitative approach and a descriptive-comparative method, this study finds that the Iranian Islamic Revolution cannot be fully understood solely through structural or spiritual lenses, but rather represents a unique synthesis of material change and ideological transformation—thereby offering a new model of revolution that transcends the conventional Western dichotomy between religion and the social.